A Cardiac Rehabilitation Program for Breast Cancer Survivors: A Feasibility Study. (28th May 2021) - Zvinovski, Filadelfiya; Stephens, Julie A.; Ramaswamy, Bhuvaneswari; Reinbolt, Raquel E.; Noonan, Anne M.; VanDeusen, Jeffrey Bryan; Wesolowski, Robert; Stover, Daniel G.; Williams, Nicole Olivia; Sardesai, Sagar D.; Mehta, Laxmi; Foraker, Randi; et al.
Abstract : Purpose . The purpose of this study was to determine the feasibility and preliminary efficacy of a cardiac rehabilitation (CR) intervention in the breast cancer population. Methods . This single-arm feasibility study evaluated a 14-week CR intervention program in breast cancer survivors. Feasibility was defined as completion of at least 30/36 sessions of the program without serious adverse events (SAE) in 80% of patients. Secondary endpoints included the change in VO2 max, cardiovascular disease (CVD) risk factors, Duke Activity Secondary Index (DASI), Brief Fatigue Inventory (BFI), and QLQ-C30. All outcomes were reported as mean change and compared using paired t -tests. Results . A total of 25 patients were enrolled in the study. 18 patients of the 25 enrolled (72%) completed the 14 weeks program without SAE. The overall adherence to the study protocol was 60%. Of the 18 participants who did not withdraw from the program, 15 (83%) adhered to the study protocol and completed 30 or more sessions. There was a nonsignificant improvement in VO2 max (mean Δ0.5, p = 0.6 ). The scores for DASI, BFI, and QLQ-C30 improved from baseline to posttreatment. Conclusion . A CR intervention in breast cancer survivors had high adherence in those who were able to complete the 14-week program. The program significantly improved patient reported physical activity, fatigue, and quality of life (QoL), without significant improvement in CVD risk factors. Implications for cancer patients are that early implementation of a CR program should be considered by practitioners as it improves QoL and exercise tolerance in breast cancer survivors.